Preparation and Characterization of Porous Yttrium Oxide Powders with High Specific Surface Area - 李永绣 林小云 王义振 罗军明 孙伟丽 (Journal of rare earths, 2006)
The porous cubic yttrium oxides with high specific surface area were prepared yttrium nitrate and its complex formed with methyl salicylate. The specific surface area by the explosive decomposition of and properties of powders synthesized at various temperatures were characterized using BET, X-ray diffraction （XRD）, infrared spectra （IR）, and scanning electron microscopy （SEM）. The results indicate that the highest specific surface area is found to be 65.37 m^2·g^-1 at the calcination temperature of 600 ℃, and then decreases to 20.33 m2· g^- 1 with the calcination temperature rising from 600 to 900 ℃. The powders show strong surface activity for adsorping water and carbon dioxide in air, which also decreases with the rising calcination temperature. The drop both on the surface area and surface activity of samples at higher temperatures may be due to pore-narrowing（sintering） effects.